Description of the eggs of Psorophora ciliata and Psorophora ferox (Diptera: Culicidae, Aedini) from the east of the Brazilian state of Santa Catarina using scanning electron microscopy - de Carvalho, Lucas Rossito; Oliveira, Eliana Medeiros; Marcondes, Carlos Brisola (Zootaxa, 2018)
Scanning electron microscopy was used to examine and describe the egg of Psorophora ciliata, which was not previous adequately described, and the egg of Ps. ferox, which exhibited regional variation. Eggs of Ps. ciliata have long tubercles (length 26.7±1.72 µm) in the outer chorion, surrounded by a hexagonal reticulation. The micropyle (external diameter, to the outer edge of the collar, 26.59 µm; internal diameter 20.8 µm) is surrounded by an irregular collar with a thickness of 14.97 ±0.63 µm. Eggs of Ps. ferox exhibit some differences in the size and shape of tubercles compared to those from other more northern regions.